Foundations for an ecological macroeconomics: Literature review and model development - Tim Jackson; Ben Drake; Peter Victor; Kurt Kratena; Mark Sommer (WWWforEurope, 2014)
This milestone provides a broad overview of model development under Work Package 205 of the WWWforEurope project. It describes briefly the challenge of modelling combined economic, ecological and financial systems and sets out a series of objectives for modelling the socio-economic transition towards sustainability. It highlights modelling needs in relation to full employment, financial stability, and social equity under conditions of constrained resource consumption and ecological limits. The paper also provides a broad overview of the literatures relevant to the task in hand. It then describes two separate modelling approaches, developed by two different teams within WWWforEurope. One of these approaches, led by WIFO, uses a Dynamic New Keynesian (DYNK) model to explore the implications of different long-run equilibrium paths for energy consumption. The other approach, led by Surrey in collaboration with York University, is motivated primarily by the desire to integrate a comprehensive model of the financial economy into a model of a (resource and emission-constrained) real economy. This paper sets out the overarching structure of each of these approaches. It discusses the similarities and differences between the two approaches and makes some proposals for the management of subsequent milestones in relation to WP 205.
Keywords: C; D; E; O; P; Q; 330; Beyond GDP; Ecological innovation; Economic strategy; Full employment growth path; Green jobs; Labour markets; Macroeconomic disequilibria; Market economy with adjectives; New technologies; Policy options; Social innovation; Socio-ecological transition; Sustainable growth; Wealth